2012
DOI: 10.1371/journal.pone.0039214
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Synergizes with IFN-γ to Upregulate iNOS and NO Production and Inhibit Chlamydial Growth

Abstract: IFN-γ-mediated inducible nitric oxide synthase (iNOS) expression is critical for controlling chlamydial infection through microbicidal nitric oxide (NO) production. Interleukin-17A (IL-17A), as a new proinflammatory cytokine, has been shown to play a protective role in host defense against Chlamydia muridarum (Cm) infection. To define the related mechanism, we investigated, in the present study, the effect of IL-17A on IFN-γ induced iNOS expression and NO production during Cm infection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 30 publications
7
49
0
Order By: Relevance
“…After IFN-␥ removal and subsequent tryptophan production, these persistent forms quickly differentiate into infectious elementary bodies. Furthermore, a recent study by Zhang and colleagues demonstrated that IFN-␥ and IL-17A synergistically inhibit Chlamydia muridarum replication by inducing intracellular iNOS and NO production (117).…”
Section: Ifn-␥mentioning
confidence: 99%
“…After IFN-␥ removal and subsequent tryptophan production, these persistent forms quickly differentiate into infectious elementary bodies. Furthermore, a recent study by Zhang and colleagues demonstrated that IFN-␥ and IL-17A synergistically inhibit Chlamydia muridarum replication by inducing intracellular iNOS and NO production (117).…”
Section: Ifn-␥mentioning
confidence: 99%
“…Notably, the role of Th17 cells in host defense against chlamydial lung infection has been recently realized. In particular, we recently reported that IFNγ and IL-17 can work synergistically to inhibit chlamydial growth (58). Therefore, the better protection in IL-10 KO mice is likely the synergistic effect of Th17 and Th1, which are both increased in these mice.…”
Section: Discussionmentioning
confidence: 95%
“…IFN‐activated human mast cells secreted IL‐17A, which may have important roles in enhancing immunity. Indeed, IL‐17A and IFNγ can act synergistically to enhance macrophage function and inhibit bacterial growth 45. Minor increases in IL‐4, IL‐13, and IL‐12 were also observed following activation with IFNγ, but not IFNα2, demonstrating differential regulation by type I and II IFNs.…”
Section: Discussionmentioning
confidence: 98%